Method for producing polymer fine particle
The method addresses the challenges of flowability and process control in producing polymer particles by polymerizing farnesene-based elastic bodies with controlled conversion rates, achieving polymer fine particles with enhanced fluidity and controllability for applications like tire modifiers.
Patent Information
- Application Number
- JP2023113204
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Existing methods for producing coated polymer particles face challenges in achieving excellent flowability and controlling internal temperature and pressure during the elastic polymerization process, particularly for particles with a volume average diameter of less than 50 nm.
A method involving the polymerization of monomer A containing farnesene to form an elastic body with a volume average particle diameter of less than 50 nm, followed by a graft portion polymerization, with a controlled polymerization conversion rate of monomer A of 20.0 (%/hour) or less, using specific initiators like para-menthane hydroperoxide, to achieve excellent controllability of internal temperature and pressure.
The method produces polymer fine particles with excellent fluidity and controllability of internal temperature and pressure, resulting in a resin composition with improved flowability and impact resistance, suitable for applications such as tire modifiers.
Smart Images

Figure 2025010904000001 
Figure 2025010904000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing polymer microparticles. [Background technology]
[0002] Coated polymer particles are used as a resin modifier for tires and the like (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2017 / 038724 Summary of the Invention [Problem to be solved by the invention]
[0004] On the other hand, the production method described in Patent Document 1 leaves room for improvement in terms of the fluidity (method B flow) of the resin composition obtained from the coated polymer particles.
[0005] Therefore, the inventors have conducted extensive research into polymer microparticles that provide resin compositions with excellent fluidity, and have newly discovered that polymer microparticles having an elastomer and a volume average particle diameter of less than 50 nm provide resin compositions with excellent fluidity.
[0006] The inventors have also newly discovered that when producing polymer microparticles having an elastomer with a volume average particle diameter of less than 50 nm, there is a problem in that it becomes difficult to control the internal temperature and internal pressure of the reaction vessel in the elastomer polymerization process.
[0007] One embodiment of the present invention has been developed in consideration of the above-mentioned problems, and its object is to provide a method for producing polymer microparticles that can provide a resin composition that has excellent controllability of internal temperature and internal pressure in the elastomer polymerization process and excellent fluidity. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and have completed the present invention. That is, one embodiment of the present invention includes the following configuration.
[0009] [1] A method for producing polymer microparticles, comprising: an elastomer polymerization step of polymerizing a farnesene-containing monomer A to obtain an elastomer containing farnesene units and having a volume average particle size of less than 50 nm; and a graft portion polymerization step of polymerizing a graft portion onto the elastomer, wherein in the elastomer polymerization step, an increase in polymerization conversion rate of the monomer A per hour is 20.0 (% / hour) or less.
[0010] [2] The method for producing polymer microparticles described in [1], wherein the polymer microparticles have the elastomer and the graft portion, and the graft portion contains more than 80% by weight of vinyl units in 100% by weight of structural units.
[0011] [3] The method for producing polymer microparticles according to [1] or [2], wherein in the elastomer polymerization step, the polymerization initiator comprises paramenthane hydroperoxide.
[0012] [4] The method for producing polymer microparticles according to any one of [1] to [3], wherein an increase in the polymerization conversion rate of the monomer A per hour is 5.0 (% / hour) or more.
[0013] [5] The method for producing polymer microparticles according to any one of [1] to [4], wherein the elastomer contains one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units and polyfunctional units.
[0014] [6] The method for producing polymer microparticles according to any one of [1] to [5], wherein the elastomer contains 5.0 wt% to 99.9 wt% of farnesene units, and 0.1 wt% to 95.0 wt% in total of one or more types of structural units selected from the group consisting of diene units, vinyl units and polyfunctional units other than farnesene units, based on 100 wt% of structural units.
[0015] [7] The method for producing polymer microparticles according to [6], wherein the elastomer contains, based on 100% by weight of constituent units, 0% by weight to 95.0% by weight of diene units other than the farnesene units, 0% by weight to 50.0% by weight of the vinyl units, and 0% by weight to 20.0% by weight of the polyfunctional units.
[0016] [8] The method for producing polymer microparticles according to any one of [1] to [7], wherein the elastic body does not contain a styrene unit and the graft portion contains a styrene unit.
[0017] [9] The method for producing polymer microparticles according to any one of [1] to [8], wherein the graft portion contains a styrene unit and / or an alkyl (meth)acrylate unit. Effect of the Invention
[0018] According to one embodiment of the present invention, it is possible to provide a method for producing polymer microparticles that can provide a resin composition that has excellent controllability of internal temperature and internal pressure in the elastomer polymerization process and excellent fluidity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments and examples obtained by appropriately combining the technical means disclosed in different embodiments and examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".
[0020] In this specification, the term "X unit" contained in a polymer, copolymer, or resin means a "structural unit derived from an X monomer." For example, the term "farnesene unit" means a "structural unit derived from a farnesene monomer."
[0021] 1. Method for Producing Polymer Microparticles A method for producing polymer microparticles according to one embodiment of the present invention includes an elastomer polymerization step of polymerizing a farnesene-containing monomer A to obtain an elastomer containing farnesene units and having a volume average particle diameter of less than 50 nm, and a graft portion polymerization step of polymerizing a graft portion onto the elastomer, wherein in the elastomer polymerization step, the increase in polymerization conversion rate of the monomer A per hour is 20.0 (% / hour) or less.
[0022] In this specification, "a method for producing polymer microparticles according to one embodiment of the present invention" may be referred to as "the present production method". Furthermore, "an elastic body according to one embodiment of the present invention" may be referred to as "the present elastic body", and "a graft portion according to one embodiment of the present invention" may be referred to as "the present graft portion".
[0023] Since the present manufacturing method has the above-mentioned configuration, it has the advantage of being able to provide a method for manufacturing polymer microparticles that can provide a resin composition that has excellent controllability of internal temperature and internal pressure in the elastomer polymerization process and excellent fluidity.
[0024] In this specification, "excellent controllability of the internal temperature in the elastomer polymerization step" means that the internal temperature of the reaction vessel in the elastomer polymerization step can be controlled within a range of ±5°C of the set internal temperature of the reaction vessel, as will be described in detail in the Examples below. That is, the present production method has the advantage that the internal temperature of the reaction vessel in the elastomer polymerization step can be controlled within a range of ±5°C of the set internal temperature of the reaction vessel.
[0025] In this specification, "excellent controllability of the internal pressure in the elastomer polymerization step" means that the internal pressure (gauge pressure) of the reaction vessel can be controlled within the range of 0 MPa to 0.8 MPa in the elastomer polymerization step, as will be described in detail in the Examples below. That is, the present production method has the advantage that the internal pressure (gauge pressure) of the reaction vessel can be controlled within the range of 0 MPa to 0.8 MPa in the elastomer polymerization step.
[0026] In the present specification, the term "a resin composition has excellent fluidity" means that, when the resin composition is subjected to the measurement of the flow rate according to the method B described later in the examples, the result is 10.0 (cm 3 / sec×10 -2 That is, when the present resin composition is subjected to the measurement of the flow rate according to the method B described later in the examples, the result is 10.0 (cm 3 / sec×10 -2 In this specification, the term "cm 3 / sec×10 -2 ) means {(cm 3 / sec)×10 -2} is intended.
[0027] In addition, this manufacturing method has the advantage that the amount of plastic used in production can be significantly reduced because the elastic material contains bio-derived farnesene. Such advantages will also contribute to the achievement of Goal 12 "Ensure sustainable consumption and production patterns" and Goal 13 "Take urgent action to mitigate climate change and its impacts" of the Sustainable Development Goals (SDGs) advocated by the United Nations.
[0028] (1-1. Elastomer Polymerization Process) The present inventors have newly discovered that a method for producing polymer microparticles having excellent controllability of internal temperature and internal pressure in the elastomer polymerization process can be provided by controlling the increase in polymerization conversion rate of monomer A per hour to 20.0 (% / hour) or less in the elastomer polymerization process.
[0029] Therefore, in an elastomer polymerization process according to one embodiment of the present invention, a farnesene-containing monomer A is polymerized to obtain an elastomer containing farnesene units and having a volume average particle size of less than 50 nm, and in the elastomer polymerization process, the increase in the polymerization conversion rate of monomer A per hour is 20.0 (% / hour) or less.
[0030] In the elastomer polymerization step, a monomer A containing farnesene is polymerized. In this specification, the monomer components used in the elastomer polymerization step are collectively referred to as "monomer A." In other words, the resulting elastomer is composed of constituent units derived from monomer A.
[0031] (1-1-1. Elastic body) The elastic body according to one embodiment of the present invention is composed of constituent units derived from a monomer A containing farnesene, and is obtained by polymerizing the monomer A.
[0032] Monomer A according to one embodiment of the present invention contains farnesene, i.e., the elastomer contains a constitutional unit derived from farnesene (farnesene unit).
[0033] Farnesene is a bio-derived diene monomer produced from biomass such as sugar cane using fermentation technology.
[0034] The farnesene contained in the monomer A may be composed of α-farnesene, β-farnesene, or both α-farnesene and β-farnesene. Compared with α-farnesene, β-farnesene is easy to manufacture and therefore easy to obtain. Therefore, it is preferable that the farnesene contained in the monomer A is composed of β-farnesene. In other words, it is preferable that the farnesene unit contained in the elastomer is composed only of β-farnesene units.
[0035] The farnesene unit preferably comprises 70% by weight, more preferably 80% by weight, further preferably 90% by weight, and particularly preferably 100% by weight of β-farnesene units out of 100% by weight of the constituent units. This configuration has the advantage that the flowability of the resulting resin composition and the impact resistance of the resulting molded article are well balanced.
[0036] The elastomer preferably contains 5.0 to 99.9% by weight of farnesene units, more preferably 25.0 to 99.9% by weight, more preferably 50.0 to 99.9% by weight, even more preferably 70.0 to 99.9% by weight, and particularly preferably 80.0 to 99.9% by weight, of 100% by weight of the constituent units. This configuration has the advantages of (i) a well-balanced and excellent flowability of the resulting resin composition and impact resistance of the resulting molded article, and (ii) excellent controllability of the internal pressure in the elastomer polymerization step.
[0037] The elastomer preferably contains one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units, and polyfunctional units (in addition to the farnesene units). In other words, the monomer A preferably contains farnesene and one or more monomers selected from the group consisting of diene monomers other than farnesene, vinyl monomers, and polyfunctional monomers. This configuration has the advantage that the flowability of the resulting resin composition and the impact resistance of the resulting molded article are well balanced.
[0038] The elastomer preferably contains, in total, 0.1% to 95.0% by weight, more preferably 0.1% to 75.0% by weight, more preferably 0.1% to 50.0% by weight, even more preferably 0.1% to 30.0% by weight, and particularly preferably 0.1% to 20.0% by weight of one or more constituent units selected from the group consisting of diene units other than farnesene units, vinyl units, and polyfunctional units, out of 100% by weight of constituent units. This configuration has the advantages of (i) providing a well-balanced and excellent flowability of the resulting resin composition and impact resistance of the resulting molded article, and (ii) providing excellent controllability of the internal pressure in the elastomer polymerization step.
[0039] The elastomer preferably contains a diene-based unit other than the farnesene unit. In other words, the monomer A preferably contains a diene-based monomer other than the farnesene unit. When the elastomer contains a diene-based unit other than the farnesene unit, a resin composition containing the polymer microparticles can provide a molded article having excellent toughness and impact resistance. A molded article having excellent toughness and / or impact resistance can also be said to be a molded article having excellent durability.
[0040] Examples of diene monomers from which the "diene units other than farnesene units" are derived include 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), and 2-chloro-1,3-butadiene. These diene monomers may be used alone or in combination of two or more. Compared with diene monomers other than farnesene and 1,3-butadiene, 1,3-butadiene is versatile and easily available. Therefore, as the diene units other than farnesene units, 1,3-butadiene units are preferred.
[0041] The diene monomer from which the "diene unit other than the farnesene unit" is derived can be referred to as a conjugated diene monomer. The elastomer preferably contains 0 to 95.0% by weight of diene units other than the farnesene unit, more preferably 0.1 to 75.0% by weight, even more preferably 1.0 to 50.0% by weight, and particularly preferably 1.0 to 30.0% by weight, of 100% by weight of the constituent units. This configuration has the advantages of providing a well-balanced flowability of the resulting resin composition and impact resistance of the resulting molded article, and excellent controllability of the internal pressure in the elastomer polymerization step.
[0042] The elastomer preferably contains a vinyl-based unit. In other words, the monomer A preferably contains a vinyl-based monomer. This configuration has the advantage that the fluidity of the resulting resin composition and the impact resistance of the resulting molded article are well balanced. In this specification, the vinyl-based monomer refers to a monomer having only one vinyl group.
[0043] Examples of vinyl monomers from which vinyl units are derived include (a) vinyl arenes such as styrene, α-methylstyrene, monochlorostyrene, and dichlorostyrene; (b) vinyl carboxylic acids such as acrylic acid and methacrylic acid; (c) salts of the vinyl carboxylic acids (such as sodium acrylate); (d) esters of the vinyl carboxylic acids (such as alkyl (meth)acrylates); (e) vinyl cyanides such as acrylonitrile and methacrylonitrile; (f) vinyl halides such as vinyl chloride, vinyl bromide, and chloroprene; (g) vinyl acetate; and (h) alkenes such as ethylene, propylene, butylene, and isobutylene. The above-mentioned vinyl monomers may be used alone or in combination of two or more. In this specification, (meth)acrylate means acrylate and / or methacrylate. In this specification, alkyl (meth)acrylate means a compound in which the portion other than the (meth)acrylate is composed only of an alkyl group.
[0044] Examples of esters of vinyl carboxylic acids include (a) alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; (b) aromatic ring-containing (meth)acrylates such as phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and phenyl (meth)acrylate; (c) hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; (d) glycidyl (meth)acrylates such as glycidyl (meth)acrylate and glycidyl alkyl (meth)acrylate; and (e) alkoxyalkyl (meth)acrylates. These (meth)acrylate monomers may be used alone or in combination of two or more. Among these (meth)acrylate monomers, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, with butyl (meth)acrylate being more preferred. According to this configuration, the glass transition temperature (Tg) of the elastomer is lowered, so that polymer microparticles having a low Tg are obtained. As a result, (a) a resin composition containing the obtained polymer microparticles can provide a molded article having excellent toughness, and (b) the viscosity of the resin composition can be further reduced.
[0045] The elastomer preferably contains 0 to 50.0% by weight of vinyl units, more preferably 0 to 45.0% by weight, even more preferably 0 to 40.0% by weight, and particularly preferably 0 to 30.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantage that the resulting molded article has excellent impact resistance.
[0046] The elastomer preferably contains a polyfunctional unit. In other words, the monomer A preferably contains a polyfunctional monomer. This configuration has the advantage that the dispersion stability of the polymer fine particles in the matrix resin can be maintained.
[0047] The polyfunctional monomer from which the polyfunctional unit is derived can be said to be a monomer having two or more radically polymerizable reactive groups in the same molecule. The radically polymerizable reactive group is preferably a carbon-carbon double bond. The polyfunctional monomer does not include butadiene, and examples thereof include (meth)acrylates having an ethylenically unsaturated double bond, such as allyl alkyl (meth)acrylates and allyloxy alkyl (meth)acrylates. Examples of monomers having two (meth)acrylic groups include ethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate (e.g., 1,3-butylene glycol di(meth)acrylate), butanediol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexane dimethanol di(meth)acrylate, and polyethylene glycol di(meth)acrylates. Examples of the polyethylene glycol di(meth)acrylates include triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and polyethylene glycol (600) di(meth)acrylate. Examples of monomers having three (meth)acrylic groups include alkoxylated trimethylolpropane tri(meth)acrylates, glycerol propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate. Examples of the alkoxylated trimethylolpropane tri(meth)acrylates include trimethylolpropane tri(meth)acrylate and trimethylolpropane triethoxy tri(meth)acrylate. Further, examples of monomers having four (meth)acrylic groups include pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, etc. Further, examples of monomers having five (meth)acrylic groups include dipentaerythritol penta(meth)acrylate, etc. Further, examples of monomers having six (meth)acrylic groups include ditrimethylolpropane hexa(meth)acrylate, etc.Polyfunctional monomers also include diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, divinylbenzene, and the like.
[0048] The polyfunctional unit is not particularly limited, but is preferably one or more selected from the group consisting of butylene glycol di(meth)acrylate unit, allyl (meth)acrylate unit, and divinylbenzene unit, and more preferably butylene glycol di(meth)acrylate unit. This configuration has the advantage that the fluidity of the resulting resin composition and the impact resistance of the resulting molded article are well balanced.
[0049] The elastic body preferably contains 0 to 20.0% by weight of the polyfunctional unit, more preferably 0.1 to 15.0% by weight, even more preferably 0.5 to 10.0% by weight, and particularly preferably 0.7 to 5.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantage that the resulting molded article has excellent impact resistance.
[0050] (Volume average particle size of elastic body) The volume average particle diameter of the elastic body is less than 50 nm, preferably 5 nm to 49 nm, more preferably 5 nm to 48 nm, even more preferably 5 nm to 45 nm, and particularly preferably 10 nm to 40 nm. When the volume average particle diameter of the elastic body is (a) 5 nm or more, an elastic body having a desired volume average particle diameter can be obtained, and when it is (b) less than 50 nm, the fluidity of the obtained resin composition and the impact resistance of the obtained molded body become good. The volume average particle diameter of the elastic body can be measured using a dynamic light scattering particle size distribution measuring device or the like, using an aqueous latex containing the elastic body as a sample. The method for measuring the volume average particle diameter of the elastic body will be described in detail in the following examples.
[0051] (Ratio of elastic body) The proportion of the elastomer in the polymer microparticles is preferably 40 to 97% by weight, more preferably 50 to 95% by weight, and even more preferably 50 to 90% by weight, based on 100% by weight of the entire polymer microparticles. When the proportion of the elastomer is 40% by weight or more, the resin composition can provide a molded article having excellent toughness and impact resistance. When the proportion of the elastomer is 97% by weight or less, the polymer microparticles do not easily aggregate (are unlikely to aggregate), and therefore are well dispersed in the resin composition. As a result, the resin composition has an excellent balance of physical properties.
[0052] In addition, the "elastic body" of the polymer microparticles is composed of elastomer 1, elastomer 2, ..., and elastomer 3, which are polymerized separately. n The "elastic body" of the polymer microparticles may include elastomer 1, elastomer 2, ..., and elastomer n may include one elastomer obtained by sequentially polymerizing each of the elastomers. In this way, an elastomer (multistage polymerized elastomer) may be produced by multistage polymerization in which a plurality of elastomers (polymers) are sequentially polymerized. In the multistage polymerized elastomer, each of the plurality of elastomers may form a layer structure. In this way, a multistage polymerized elastomer in which each of the plurality of elastomers forms a layer structure can also be called a multilayered elastomer. That is, in one embodiment of the present invention, the "elastic body" of the polymer microparticles may include (a) a composite of a plurality of elastomers, (b) a multistage polymerized elastomer, and / or (c) a multilayered elastomer.
[0053] (Method of Polymerizing Monomer A) The polymerization method of the monomer A is not particularly limited as long as the increase in the polymerization conversion rate per hour is 20.0 (% / hour) or less. The "polymerization of the monomer A" can also be called "polymerization of an elastomer."
[0054] The polymerization of the monomer A can be carried out by, for example, a method such as emulsion polymerization, suspension polymerization, or microsuspension polymerization.
[0055] In the polymerization of monomer A, the method for adjusting the increase in polymerization conversion rate per hour to 20.0 (% / hour) or less is not particularly limited. In the polymerization of monomer A, for example, the type of polymerization initiator, the amount of polymerization initiator used, the method of adding the polymerization initiator, the polymerization temperature, the type of monomer, etc. can be adjusted to make the increase in polymerization conversion rate per hour 20.0 (% / hour) or less.
[0056] A polymerization initiator may be used in the polymerization of the monomer A. The polymerization initiator is not particularly limited, but may be, for example, one or more appropriately selected from the group consisting of peroxides, azo compounds, potassium persulfate, and the like.
[0057] Examples of peroxides include paramenthane hydroperoxide, benzoyl peroxide, cumene hydroperoxide, dicumyl peroxide, diisopropylbenzene hydroperoxide, t-butyl hydroperoxide, t-butyl peroxyacetate, t-butyl peroxybenzoate, t-butyl isopropyl carbonate, di-t-butyl peroxide, t-butyl peroctate, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and t-butylperoxy-2-ethylhexanoate. Among these, paramenthane hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide are particularly preferably used.
[0058] Examples of azo compounds include azobisisobutyronitrile, azobis(2,4-dimethylvaleronitrile), 2-phenylazo-2,4-dimethyl-4-methoxyvaleronitrile, 2-cyano-2-propylazoformamide, 1,1'-azobiscyclohexane-1-carbonitrile, azobis(4-methoxy-2,4-dimethylvaleronitrile), dimethyl 2,2'-azobisisobutyrate, 1-t-butylazo-2-cyanobutane, and 2-t-butylazo-2-cyano-4-methoxy-4-methylpentane.
[0059] In the elastomer polymerization step, the polymerization initiator used is preferably one or more selected from the group consisting of paramenthane hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide, more preferably paramenthane hydroperoxide or cumene hydroperoxide, and particularly preferably paramenthane hydroperoxide. This configuration has the advantage that the polymer microparticles can be polymerized with good productivity.
[0060] In the elastomer polymerization step, the total amount of the polymerization initiator used is not particularly limited, but is preferably 0.03 to 3.00 parts by weight, more preferably 0.05 to 2.50 parts by weight, and particularly preferably 0.10 to 2.00 parts by weight, relative to 100 parts by weight of the monomer A. This configuration has the advantage that the polymer microparticles can be polymerized safely and with good productivity.
[0061] From the viewpoint of controlling the increase in polymerization conversion rate per hour to 20.0 (% / hour) or less, a preferred method of adding the polymerization initiator includes, for example, a method in which the polymerization initiator is added in equal amounts immediately after the lump-sum addition of the monomer components used in producing the elastomer (0 hours after the lump-sum addition) and in several portions at hourly intervals after the lump-sum addition.
[0062] The number of times the polymerization initiator is added is not particularly limited, but is preferably 5 to 15, more preferably 6 to 14, further preferably 7 to 13, and particularly preferably 8 to 12. This configuration has the advantage that the polymer microparticles can be polymerized safely and with good productivity.
[0063] The polymerization temperature of the monomer A in the elastomer polymerization step (i.e., the internal temperature of the reaction vessel) is not particularly limited, but is preferably 30° C. to 80° C., more preferably 35° C. to 75° C., further preferably 35° C. to 70° C., and particularly preferably 35° C. to 65° C. This configuration has the advantage that the polymer microparticles can be polymerized safely and with good productivity.
[0064] The increase in the polymerization conversion rate of monomer A per hour is 20.0 (% / hour) or less, preferably 18.0 (% / hour) or less, more preferably 16.0 (% / hour) or less, even more preferably 14.0 (% / hour) or less, and particularly preferably 12.0 (% / hour) or less. This configuration has the advantage of providing a method for producing polymer microparticles that is excellent in controllability of the internal temperature and internal pressure during polymerization of monomer A. The method for measuring the increase in the polymerization conversion rate of monomer A per hour will be described in detail in the following examples.
[0065] The increase in the polymerization conversion rate of monomer A per hour is preferably 5.0 (% / hour) or more, more preferably 6.0 (% / hour) or more, even more preferably 7.0 (% / hour) or more, and particularly preferably 8.0 (% / hour) or more. This configuration has the advantage that polymer microparticles can be polymerized with good productivity. The method for measuring the increase in the polymerization conversion rate of monomer A per hour will be described in detail in the following examples.
[0066] The converted polymerization time is not particularly limited, but is preferably within 20.0 hours, more preferably within 15.0 hours, even more preferably within 13.0 hours, and particularly preferably within 10.0 hours. According to this configuration, it can be said that the polymer microparticles can be polymerized with good productivity. The method for measuring the converted polymerization time will be described in detail in the following examples.
[0067] In the elastomer polymerization step, the internal temperature of the reaction vessel is preferably controlled within a range of ±5°C of the set value of the internal temperature of the reaction vessel. This configuration can be said to provide excellent controllability of the internal temperature in the elastomer polymerization step. The method for measuring the internal temperature of the reaction vessel will be described in detail in the following examples.
[0068] In addition, in the elastomer polymerization step, the internal pressure (gauge pressure) of the reaction vessel is preferably 0 MPa to 0.8 MPa. According to this configuration, it can be said that the controllability of the internal pressure in the elastomer polymerization step is excellent. The method for measuring the internal pressure of the reaction vessel will be described in detail in the following examples.
[0069] (1-2. Graft Polymerization Step) In the graft portion polymerization step according to one embodiment of the present invention, the graft portion is polymerized onto the elastomer.
[0070] (Graft part) In this specification, a polymer grafted to an elastomer, and a polymer grafted to a polymer grafted to an elastomer, are referred to as a graft portion.
[0071] The graft moiety preferably contains a vinyl-based unit. The graft moiety has the above-mentioned structure, and therefore can play various roles. The "various roles" include, for example, (a) improving the compatibility between the resin component in the resin composition and the polymer fine particles, (b) improving the dispersibility of the polymer fine particles in the resin composition and in the molded product, and (c) enabling the polymer fine particles to be dispersed in the form of primary particles in the resin composition and in the molded product.
[0072] The graft portion preferably contains vinyl units in an amount of more than 80% by weight, more preferably 85% by weight or more, even more preferably 90% by weight or more, even more preferably 95% by weight or more, and particularly preferably 100% by weight (i.e., the graft portion is made of vinyl units) out of 100% by weight of the constituent units. This configuration has the advantage that the polymer fine particles can provide a powder or granule having excellent powder properties.
[0073] A powder or granule having excellent powder characteristics has the advantage that the powder or granule can be mixed well with a matrix resin to be mixed. In particular, when a powder-like matrix resin such as polyvinyl chloride (PVC) is mixed with a powder or granule in order to modify the powder-like matrix resin such as polyvinyl chloride (PVC), it is preferable to use a powder or granule having excellent powder characteristics.
[0074] The vinyl-based unit is preferably a structural unit derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyan monomer, and a (meth)acrylate monomer.
[0075] Specific examples of aromatic vinyl monomers include styrene, α-methylstyrene, and p-methylstyrene.
[0076] Specific examples of vinyl cyanide monomers include acrylonitrile and methacrylonitrile.
[0077] Specific examples of the (meth)acrylate monomer include the same monomers as the alkyl (meth)acrylate monomers described above.
[0078] The one or more monomers selected from the group consisting of the aromatic vinyl monomer, the vinyl cyan monomer, and the (meth)acrylate monomer may be used alone or in combination of two or more.
[0079] The graft portion preferably contains aromatic vinyl units, vinyl cyan units and (meth)acrylate units in a total amount of 10.0% by weight to 100% by weight, more preferably 30.0% by weight to 100.0% by weight, more preferably 50.0% by weight to 100% by weight, particularly preferably 60.0% by weight to 100% by weight, and most preferably 70.0% by weight to 100% by weight. This configuration has the advantages of being able to provide a powdery granule in which the polymer fine particles have excellent powder characteristics, being able to improve the compatibility between the resin component in the resin composition and the polymer fine particles, and being able to improve the dispersibility of the polymer fine particles in the resin composition and in the molded product.
[0080] The graft portion preferably contains a styrene unit and / or an alkyl (meth)acrylate unit. This configuration has the advantages of providing a powdered granule in which the polymer fine particles have excellent powder characteristics, improving the compatibility between the resin component in the resin composition and the polymer fine particles, and improving the dispersibility of the polymer fine particles in the resin composition and in the molded product.
[0081] The graft portion preferably contains 10.0 to 100% by weight of (meth)acrylate units, more preferably 30.0 to 100% by weight, even more preferably 50.0 to 100% by weight, and particularly preferably 70.0 to 100% by weight, based on 100% by weight of the structural units. This configuration has the advantage of providing good compatibility with the matrix resin to be mixed.
[0082] It is preferred that the elastomer does not contain a styrene unit and the graft portion contains a styrene unit, which has the advantage that the flexibility of the elastomer is maintained and the resulting molded article has excellent impact resistance.
[0083] When the graft portion contains a styrene unit, the content of the styrene unit is preferably 5.0% by weight to 100% by weight, more preferably 10.0% by weight to 90.0% by weight, more preferably 10.0% by weight to 85.0% by weight, even more preferably 10.0% by weight to 80.0% by weight, and particularly preferably 10.0% by weight to 70.0% by weight, based on 100% by weight of the constituent units of the graft portion. This configuration has the advantage that the obtained molded article has excellent impact resistance and transparency.
[0084] The graft portion may contain, as constituent units, a diene-based unit and a polyfunctional unit.
[0085] When the graft portion contains a polyfunctional unit, it has the following advantages: (a) swelling of the polymer microparticles in the resin composition can be prevented; (b) the viscosity of the resin composition is reduced, so that the handleability of the resin composition tends to be improved; and (c) the dispersibility of the polymer microparticles in the resin composition is improved.
[0086] When the graft portion contains a diene unit and a polyfunctional unit as constituent units, the content is not particularly limited, but is preferably less than 20.0% by weight, more preferably 15.0% by weight or less, more preferably 10.0% by weight or less, even more preferably 5.0% by weight or less, and particularly preferably 0% by weight, based on 100% by weight of the constituent units of the graft portion. This configuration has the advantage that the polymer fine particles can provide a powder or granule having excellent powder properties.
[0087] The graft portion preferably does not contain a diene unit. When the graft portion is a multilayer, it is particularly preferable that the outermost layer does not contain a diene unit. When the graft portion (e.g., the outermost layer) does not contain a diene unit, polymer microparticles having a graft portion (outermost layer) with a Tg of a certain level or higher (e.g., 10°C or higher, preferably 20°C or higher, 30°C or higher, 40°C or higher, or 50°C or higher) can be obtained, which has the advantage of providing a powder or granule with excellent powder properties.
[0088] When the graft portion does not contain a polyfunctional unit, the resin composition can provide a molded article having superior toughness and impact resistance, as compared with when the graft portion contains a polyfunctional unit.
[0089] The polyfunctional monomer that can be used in the polymerization of the graft portion includes the same monomers as the polyfunctional monomers described above.
[0090] (Proportion of graft area) The proportion of the graft portion in the polymer microparticles is preferably 10% by weight to 70% by weight, more preferably 15% by weight to 60% by weight, and even more preferably 20% by weight to 50% by weight, based on 100% by weight of the entire polymer microparticles. When the proportion of the graft portion is 10% by weight or more, it is advantageous that the polymer microparticles can provide a powdered granular material having excellent powder characteristics. When the proportion of the elastic body is 70% by weight or less, it is advantageous that a molded product having excellent impact resistance can be provided.
[0091] The graft portion is composed of graft portion 1, graft portion 2, . . . and graft portion n The graft portion may include a composite of graft portion 1, graft portion 2, ..., and graft portion n In this manner, a multi-stage polymerization graft portion may be produced by multi-stage polymerization of a plurality of types of graft portions.
[0092] When the graft portion is composed of multiple types of graft portions, not all of these multiple types of graft portions need to be graft-bonded to the elastomer. At least a portion of at least one type of graft portion may be graft-bonded to the elastomer, and the other types (multiple other types) of graft portions may be graft-bonded to the graft portion graft-bonded to the elastomer.
[0093] Graft portion 1, graft portion 2, ..., and graft portion nIn the multi-stage polymerization graft portion, n The graft part n-1 or a graft portion. n-1 In the multi-stage polymerization graft portion, n Part of the graft n-1 Sometimes it penetrates inside the
[0094] In the multi-stage polymerization graft portion, each of the multiple graft portions may form a layer structure. For example, when the multi-stage polymerization graft portion is composed of graft portions 1, 2, and 3, an embodiment in which graft portion 1 forms the innermost layer in the graft portion, a layer of graft portion 2 is formed on the outer side of graft portion 1, and a layer of graft portion 3 is formed as the outermost layer on the outer side of the layer of graft portion 2 is also one aspect of the present invention. In this way, a multi-stage polymerization graft portion in which each of the multiple graft portions forms a layer structure can also be called a multi-layer graft portion. That is, in one embodiment of the present invention, the graft portion may include (a) a mixture of multiple types of graft portions, (b) a multi-stage polymerization graft portion, and / or (c) a multi-layer graft portion.
[0095] When the elastomer and the graft portion are polymerized in this order in the production of polymer microparticles, at least a portion of the graft portion can cover at least a portion of the elastomer in the resulting polymer microparticles. Polymerization of the elastomer and the graft portion in this order can be said to be multistage polymerization of the elastomer and the graft portion. The polymer microparticles obtained by multistage polymerization of the elastomer and the graft portion can also be said to be multistage polymers.
[0096] When the polymer microparticles are multi-stage polymers, the graft portion may cover at least a portion of the elastomer, or may cover the entire elastomer. When the polymer microparticles are multi-stage polymers, a portion of the graft portion may penetrate into the inside of the elastomer.
[0097] When the polymer microparticles are multistage polymers, the elastomer and the graft portion may form a layer structure. For example, an embodiment in which the elastomer forms the innermost layer (also referred to as a core layer) and the layer of the graft portion is formed as the outermost layer (also referred to as a shell layer) on the outside of the elastomer is also one aspect of the present invention. A structure in which the elastomer is the core layer and the graft portion is the shell layer can also be called a core-shell structure. Thus, polymer microparticles in which the elastomer and the graft portion form a layer structure (core-shell structure) can also be called multilayer polymers or core-shell polymers. That is, in one embodiment of the present invention, the polymer microparticles may be multistage polymers and / or multilayer polymers or core-shell polymers. However, as long as the graft portion is graft-bonded to the elastomer, the polymer microparticles are not limited to the above structure.
[0098] At least a part of the graft portion preferably covers at least a part of the elastomer. In other words, at least a part of the graft portion preferably exists on the outermost side of the polymer fine particles. This configuration has the advantages that the polymer fine particles can provide a powdery product having excellent powder characteristics, the compatibility between the resin component in the resin composition and the polymer fine particles can be improved, and the dispersibility of the polymer fine particles in the resin composition and in the molded product can be improved.
[0099] The polymer microparticles preferably comprise an elastomer and a graft portion. The graft portion is preferably present on the outermost side of the polymer microparticles. This configuration has the advantages of providing a powdered granular product in which the polymer microparticles have excellent powder characteristics, improving the compatibility between the resin component in the resin composition and the polymer microparticles, and improving the dispersibility of the polymer microparticles in the resin composition and in the molded product.
[0100] (Method of manufacturing the graft part) The graft portion can be formed, for example, by polymerizing the monomer used for forming the graft portion by known radical polymerization. When (a) the elastomer or (b) the polymer microparticle precursor containing the elastomer is obtained as an aqueous latex, the polymerization of the graft portion is preferably carried out by emulsion polymerization. The graft portion can be produced, for example, according to the method described in WO2005 / 028546.
[0101] The graft portion is a portion having a plurality of types of graft portions (e.g., graft portion 1, graft portion 2, ..., graft portion n A method for producing a graft portion in the case where the graft portion is composed of graft portion 1, graft portion 2, ..., graft portion n may be polymerized separately by the above-mentioned method, and then mixed and composited to produce a graft portion (composite) consisting of a plurality of types of graft portions. Alternatively, graft portion 1, graft portion 2, ..., graft portion n may be sequentially polymerized in multiple stages to produce one graft moiety consisting of multiple types of graft moieties.
[0102] When emulsion polymerization is employed as a method for producing polymer fine particles, a known emulsifier (dispersant) can be used for producing the polymer fine particles.
[0103] Examples of emulsifiers include anionic emulsifiers, nonionic emulsifiers, polyvinyl alcohol, alkyl-substituted cellulose, polyvinylpyrrolidone, polyacrylic acid derivatives, etc. Examples of anionic emulsifiers include sulfur-based emulsifiers, phosphorus-based emulsifiers, sarcosinic acid-based emulsifiers, carboxylic acid-based emulsifiers, etc. Examples of sulfur-based emulsifiers include sodium dodecylbenzenesulfonate (abbreviation: SDBS), sodium lauryl sulfate, etc. Examples of phosphorus-based emulsifiers include sodium polyoxyethylene lauryl ether phosphate, tripotassium phosphate, etc.
[0104] When the emulsion polymerization method is used as the method for producing the polymer microparticles, a thermally decomposable initiator can be used for producing the polymer microparticles. Examples of the thermally decomposable initiator include known initiators such as 2,2'-azobisisobutyronitrile and (b) peroxides such as organic peroxides and inorganic peroxides. Examples of the organic peroxides include t-butylperoxyisopropyl carbonate, paramenthane hydroperoxide, cumene hydroperoxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, and t-hexyl peroxide. Examples of the inorganic peroxides include hydrogen peroxide, potassium persulfate, and ammonium persulfate.
[0105] A redox type initiator can also be used to produce polymer microparticles. The redox type initiator is an initiator that uses (a) a peroxide such as an organic peroxide or an inorganic peroxide in combination with (b) a transition metal salt such as ferrous sulfate (FeSO4·7H2O), or a reducing agent such as sodium formaldehyde sulfoxylate or glucose. If necessary, a chelating agent such as disodium ethylenediaminetetraacetate, and if necessary, a phosphorus-containing compound such as sodium pyrophosphate, may also be used in combination.
[0106] When a redox type initiator is used, polymerization can be performed even at a low temperature where the peroxide does not substantially decompose thermally, and the polymerization temperature can be set in a wide range. Therefore, it is preferable to use a redox type initiator. Among redox type initiators, redox type initiators using organic peroxides such as cumene hydroperoxide, dicumyl peroxide, paramenthane hydroperoxide, and t-butyl hydroperoxide as peroxides are preferable. The amount of the initiator used, and the amount of the reducing agent, transition metal salt, chelating agent, etc. used when a redox type initiator is used can be within a known range.
[0107] When a polyfunctional monomer is used in the polymerization of the elastomer or the graft portion for the purpose of introducing a crosslinked structure into the elastomer or the graft portion, a known chain transfer agent can be used in a known amount range. By using the chain transfer agent, the molecular weight and / or degree of crosslinking of the obtained elastomer or the graft portion can be easily adjusted.
[0108] In the production of the polymer microparticles, in addition to the above-mentioned components, a surfactant may be further used. The type and amount of the surfactant used are within the known ranges.
[0109] In the production of polymer microparticles, the polymerization conditions such as polymerization temperature, pressure, and deoxidation may be appropriately set within known numerical ranges.
[0110] (1-3. Physical properties of polymer particles) The physical properties of the polymer fine particles will be described below.
[0111] (Volume average particle size of polymer particles) The volume average particle diameter of the polymer microparticles is not particularly limited, but is preferably less than 50 nm, more preferably 5 nm to 49 nm, more preferably 5 nm to 48 nm, even more preferably 5 nm to 45 nm, and particularly preferably 10 nm to 40 nm. When the volume average particle diameter of the polymer microparticles is within the above range, there is also an advantage that the dispersibility of the polymer microparticles in the resin composition is good. In this specification, the "volume average particle diameter of the polymer microparticles" refers to the volume average particle diameter of the primary particles of the polymer microparticles, unless otherwise specified. The volume average particle diameter of the polymer microparticles can be measured using a dynamic light scattering particle size distribution measuring device or the like, using an aqueous latex containing the polymer microparticles as a sample. The volume average particle diameter of the polymer microparticles will be described in detail in the following examples. The volume average particle diameter of the polymer microparticles can also be measured by cutting a molded body of the resin composition, photographing the cut surface using an electron microscope or the like, and using the obtained imaging data (photographed image).
[0112] As described above, the present production method can provide polymer microparticles that can provide a resin composition with excellent fluidity, and has excellent controllability of the internal temperature and internal pressure in the elastomer polymerization step. As described below, the polymer microparticles obtained by the present production method can provide a resin composition that can provide a molded product with excellent impact resistance by mixing with polyvinyl chloride (PVC). In other words, the polymer microparticles obtained by the present production method can be suitably used as a modifier for polyvinyl chloride. Therefore, one embodiment of the present invention can be said to be a method for producing a modifier for polyvinyl chloride.
[0113] An embodiment of the present invention may be configured as follows: an elastomer polymerization step of polymerizing a farnesene-containing monomer A to obtain an elastomer containing farnesene units and having a volume average particle size of less than 50 nm; A graft portion polymerization step of polymerizing a graft portion onto the elastomer, A method for producing a modifier for polyvinyl chloride, wherein in the elastomer polymerization step, an increase in polymerization conversion rate of the monomer A per hour is 20.0 (% / hour) or less.
[0114] [2. Powder] A powder according to one embodiment of the present invention (hereinafter, sometimes referred to as "the present powder") contains polymer microparticles obtained by the manufacturing method described in the above section [1. Manufacturing method of polymer microparticles]. Since the present powder has the above-mentioned constitution, it has the advantage that it is possible to provide a resin composition having excellent fluidity and a molded body having excellent impact resistance. For example, a resin composition can be obtained by blending (adding) the present powder to any resin. A molded body obtained by molding the resin composition has the advantage of having excellent impact resistance. Furthermore, since the present powder has the above-mentioned constitution, it also has the advantage of having excellent powder properties.
[0115] In this specification, the term "particulate material" includes both powder and granules, and refers to an aggregate of powder, granules, etc. In addition, when making a particular distinction, "powder" refers to a material having a volume average particle diameter of 0.01 mm to 0.1 mm, and "granules" refers to a material having a volume average particle diameter of 0.1 mm to 10 mm. However, the particulate material may contain coarse particles of 10 mm or more. The "volume average particle diameter" in the range of less than 10 μm can be measured using a dynamic light scattering (DLS) particle size distribution analyzer Nanotrac WaveII-EX150 (manufactured by Microtrack Bell Co., Ltd.), and the "volume average particle diameter" in the range of 10 μm or more can be measured using a laser diffraction particle size distribution analyzer Microtrack MT3000II (manufactured by Microtrack Bell Co., Ltd.).
[0116] (2-1. Other optional ingredients) The powder may contain optional components other than the polymer microparticles, as necessary. Examples of the optional components include curing agents, colorants such as pigments and dyes, extender pigments, pigment dispersants, UV absorbers, the above-mentioned antioxidants, heat stabilizers (gelling inhibitors), plasticizers, leveling agents, defoamers, silane coupling agents, antistatic agents, flame retardants, lubricants, viscosity reducers, viscosity adjusters, thixotropic agents, low-shrinkage agents, inorganic fillers, organic fillers, thermoplastic resins, drying agents, dispersants, thermal conductivity improvers, water binding agents, anti-sagging agents, color separation inhibitors, anti-settling agents, coating wear adjusters, surface adjusters, monobasic organic acids, camphor, castor oil, etc.
[0117] These other optional components can be added at any stage in the production of the powder or granule. For example, they may be added during the production (polymerization) of the polymer microparticles, they may be added to the aqueous latex of the polymer microparticles, or they may be added to the powder or granule.
[0118] (2-2. Manufacturing method of powder and granular materials) The method for producing the powder or granule can be embodied, for example, in the following manner: A preparation step of preparing polymer microparticles; an aggregating step of aggregating the polymer fine particles; a drying step of drying the aggregate obtained in the aggregation step.
[0119] More specifically, the method for producing powder or granular material according to one embodiment of the present invention can be implemented, for example, as follows: A preparation step of preparing polymer microparticles; an aggregating step of aggregating the polymer fine particles; A drying step of drying the aggregate obtained in the aggregation step, The preparation step comprises: an elastomer polymerization step of polymerizing a farnesene-containing monomer A to obtain an elastomer containing farnesene units and having a volume average particle size of less than 50 nm; A graft portion polymerization step of polymerizing a graft portion onto the elastomer, A method for producing powder or granular material, wherein in the elastomer polymerization step, an increase in polymerization conversion rate of the monomer A per hour is 20.0 (% / hour) or less.
[0120] (Preparation process) Specific examples of the preparation process are the same as those described in the above section [1. Method for producing polymer microparticles], so the description is incorporated herein by reference and will not be described here.
[0121] (agglomeration process) The aggregation step is not particularly limited as long as it can finally obtain an aggregate of polymer fine particles.
[0122] The method of aggregating the polymer microparticles is not particularly limited. Examples of the method of aggregating the polymer microparticles include known methods such as a method using a coagulant, a method using a solvent, and a method of spraying an aqueous latex of polymer microparticles. Here, the mixture containing the aggregate of polymer microparticles and the aqueous solvent obtained by aggregating the polymer microparticles in the aqueous latex is also called a slurry.
[0123] As a method for aggregating the polymer fine particles, it is preferable to adopt a method using a coagulant, in other words, it is preferable to use a coagulant in the aggregating step.
[0124] Examples of the coagulant include an aqueous solution of an inorganic salt, an aqueous solution of an inorganic acid, an aqueous solution of an organic salt, an aqueous solution of an organic acid, and a polymeric coagulant.
[0125] Examples of inorganic salts include chloride salts, bromide salts, iodide salts, sulfate salts, nitrate salts, ammonium salts, and phosphate salts. Specific examples of inorganic salts include sodium chloride, potassium chloride, lithium chloride, sodium bromide, potassium bromide, lithium bromide, potassium iodide, sodium iodide, potassium sulfate, sodium sulfate, ammonium sulfate, ammonium chloride, sodium nitrate, potassium nitrate, calcium chloride, ferrous sulfate, magnesium sulfate, zinc sulfate, copper sulfate, barium chloride, ferrous chloride, ferric chloride, magnesium chloride, ferric sulfate, aluminum sulfate, potassium alum, and iron alum.
[0126] Examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.
[0127] The coagulant may be used alone or in combination of two or more. As the coagulant, an aqueous solution of a monovalent or divalent inorganic salt or an inorganic acid such as sodium chloride, potassium chloride, sodium sulfate, ammonium chloride, calcium chloride, magnesium chloride, magnesium sulfate, barium chloride, hydrochloric acid, or sulfuric acid can be suitably used. There is no particular limitation on the method of adding the coagulant, and it can be added all at once, in portions, or continuously.
[0128] As the coagulant, only one of the above-mentioned compounds may be used, or two or more of them may be used in combination. As the coagulant, among the above-mentioned compounds, an aqueous solution of monovalent or divalent inorganic salt or inorganic acid such as sodium chloride, potassium chloride, sodium sulfate, ammonium chloride, calcium chloride, magnesium chloride, magnesium sulfate, barium chloride, hydrochloric acid, or sulfuric acid can be preferably used. There is no particular limitation on the method of adding the coagulant, and it can be added all at once, added in portions, or added continuously.
[0129] In one embodiment of the present invention, the polymer microparticles can be aggregated by contacting the aqueous latex containing the polymer microparticles with a coagulant or a solution of the coagulant (e.g., an aqueous solution). The method of contacting the aqueous latex containing the polymer microparticles with the coagulant or the solution of the coagulant is not particularly limited. Examples of the method include (i) a method of contacting the aqueous latex containing the polymer microparticles with a coagulant or a solution of the coagulant, and (ii) (ii-a) a method of contacting droplets containing polymer microparticles obtained by spraying the aqueous latex containing the polymer microparticles with (ii-b) a coagulant or a solution of the coagulant, or a solution of the coagulant solution.
[0130] In one embodiment of the present invention, a slurry containing agglomerates of polymeric particles can be obtained by contacting an aqueous latex containing polymeric particles with a coagulant or a solution of a coagulant.
[0131] The aggregating step may further include a heat treatment step of heat-treating (heating) the slurry. By carrying out the heat treatment step, it is possible to obtain a powder having more excellent powder properties.
[0132] The agglomeration step may further include a recovery step of recovering the resulting agglomerates from the slurry.
[0133] The recovery step is not particularly limited as long as it can separate the aqueous solvent of the slurry from the aggregates, and any known method can be used. Examples of the recovery step include a method of filtering the slurry and a method of centrifugal dehydration of the slurry.
[0134] (drying process) The drying step is a step of drying the aggregate of polymer microparticles obtained by the above-mentioned aggregation step. The method for drying the aggregate is not particularly limited, and examples thereof include static drying, flash drying, and freeze drying.
[0135] In this specification, the term "static drying" refers to a mode in which an aggregate of polymer fine particles is dried by being statically left in a container such as an oven.
[0136] In this specification, the term "airflow drying" refers to a mode in which the aggregates are dried while being airborne in a certain space. The airflow drying method is not particularly limited, and any conventionally known method can be used. One example of airflow drying is a method in which the aggregates are placed in a container and a gas at a predetermined temperature is fed into the container to dry the aggregates while being airborne in the container.
[0137] In this specification, the term "airflow drying" refers to drying the aggregates while they are airborne in a certain space. The airflow drying method is not particularly limited, and any conventionally known method can be used. One example of airflow drying is a method in which the aggregates are placed in a container and a gas at a predetermined temperature is fed into the container to dry the aggregates while they are airborne in the container.
[0138] The method of freeze-drying is not particularly limited, and any conventionally known method can be used. When freeze-drying is used as the drying step, the drying step can be easily carried out at 0° C. or lower.
[0139] (Cleaning process) Between the aggregating step and the drying step, a washing step of washing the aggregate obtained in the aggregating step with washing water (for example, tap water, ion-exchanged water or pure water) may be further included.
[0140] As described below, the powder according to one embodiment of the present invention can be mixed with polyvinyl chloride (PVC) to provide a resin composition that can provide a molded article having excellent impact resistance. In other words, the powder according to one embodiment of the present invention can be suitably used as a modifier for polyvinyl chloride. Therefore, the method for producing the powder according to one embodiment of the present invention can also be said to be a method for producing a modifier for polyvinyl chloride.
[0141] An embodiment of the present invention may be configured as follows: A preparation step of preparing polymer microparticles; an aggregating step of aggregating the polymer fine particles; A drying step of drying the aggregate obtained in the aggregation step, The preparation step comprises: an elastomer polymerization step of polymerizing a farnesene-containing monomer A to obtain an elastomer containing farnesene units and having a volume average particle size of less than 50 nm; A graft portion polymerization step of polymerizing a graft portion onto the elastomer, A method for producing a modifier for polyvinyl chloride, wherein in the elastomer polymerization step, an increase in polymerization conversion rate of the monomer A per hour is 20.0 (% / hour) or less.
[0142] [3. Resin composition] A resin composition according to one embodiment of the present invention (hereinafter, sometimes referred to as "this resin composition") is a resin composition containing polymer microparticles obtained by the manufacturing method described in the above section [1. Manufacturing method of polymer microparticles] and a matrix resin. The present resin composition also includes a resin composition containing the powder particles described in the above section [2. Powder particles] and a matrix resin. Since the resin composition according to one embodiment of the present invention has the above-mentioned configuration, it has the advantage of being able to provide a molded product with excellent flowability and impact resistance.
[0143] (Matrix resin) Examples of the matrix resin include thermoplastic resins such as acrylic polymers, vinyl copolymers, polycarbonates, polyamides, polyesters, polyphenylene ethers, polyurethanes, and polyvinyl acetates, etc. These may be used alone or in combination of two or more.
[0144] The acrylic polymer is a polymer mainly composed of a structural unit made of an acrylic acid ester monomer. The acrylic acid ester monomer preferably has an ester moiety having 1 to 20 carbon atoms. Examples of the acrylic polymer include (a) a homopolymer of an acrylic acid ester monomer, and (b) a copolymer of an acrylic acid ester monomer with a monomer such as an unsaturated fatty acid, an acrylamide monomer, a maleimide monomer, or vinyl acetate, or a vinyl copolymer (hereinafter also referred to as an acrylic copolymer).
[0145] The vinyl copolymer is obtained by copolymerizing a mixture of vinyl monomers containing at least one monomer selected from the group consisting of an aromatic vinyl monomer, a cyanide vinyl monomer, and an unsaturated carboxylic acid alkyl ester monomer. The mixture of vinyl monomers may further contain other monomers copolymerizable with the above-mentioned monomers.
[0146] Specific examples of vinyl copolymers include polyvinyl chloride (PVC), chlorinated polyvinyl chloride, polystyrene, styrene-acrylonitrile copolymer, styrene-acrylonitrile-N-phenylmaleimide copolymer, α-methylstyrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene copolymer, etc. These may be used alone or in combination of two or more.
[0147] Examples of polyesters include polyethylene terephthalate and polybutylene terephthalate, etc. In addition, examples of the polyesters include aliphatic polyesters, plant-derived resins such as polylactic acid, and biodegradable resins.
[0148] The matrix resin is preferably polyvinyl chloride. This configuration has the advantage that it is possible to provide a resin composition having excellent flowability and a molded article having excellent impact resistance.
[0149] (Other optional ingredients) The resin composition may contain other optional components other than the matrix resin, as necessary. Examples of the other optional components include a curing agent, a coloring agent such as a pigment or dye, a body pigment, a pigment dispersant, an ultraviolet absorber, the above-mentioned antioxidant, a heat stabilizer (gelling inhibitor), a plasticizer, a leveling agent, an antifoaming agent, a silane coupling agent, an antistatic agent, a flame retardant, a lubricant, a viscosity reducing agent, a viscosity adjusting agent, a thixotropic agent, a shrinkage reducing agent, an inorganic filler, an organic filler, a thermoplastic resin, a drying agent, a dispersing agent, a thermal conductivity improving agent, a water binding agent, an anti-sagging agent, a color separation preventing agent, an anti-settling agent, a coating wear adjusting agent, a surface adjusting agent, a monobasic organic acid, camphor, castor oil, etc.
[0150] (Fluidity of Resin Composition) The flow rate of the resin composition is 10(cm 3 / sec×10 -2 ), and preferably greater than 12 (cm 3 / sec×10 -2 ) or more, and 14 (cm 3 / sec×10 -2 ) or more. According to this configuration, it can be said that the resin composition has excellent fluidity. The method for measuring the flow rate of the resin composition by method B will be described in detail in the examples below.
[0151] (Method of producing resin composition) The method for producing a resin composition according to one embodiment of the present invention includes a step of mixing the polymer microparticles obtained by the method described in Section 1. Method for producing polymer microparticles with a matrix resin. This method makes it possible to obtain a resin composition in which the polymer microparticles are uniformly dispersed in the matrix resin.
[0152] Regarding the method for producing the resin composition, various components and specific steps are not particularly limited, and the above explanations are appropriately used.
[0153] The specific method for mixing the powder and the matrix resin is not particularly limited, and examples of the method include a method using a rotation / revolution mixer, a planetary mixer, a disperser, etc. A preferred method for mixing the polymer fine particles and the matrix resin is, for example, a method in which the polymer fine particles and the matrix resin are mixed using a rotation / revolution mixer at 2000 rpm for 40 minutes.
[0154] Furthermore, the method for producing the resin composition may include a step of washing the obtained resin composition. By washing the resin composition, a resin composition containing fewer impurities can be produced.
[0155] Furthermore, the method for producing a resin composition according to one embodiment of the present invention may include other steps. In addition to the above-mentioned steps, the method may include a step of heating the obtained resin composition and devolatilizing and drying it. Various methods can be used for such a step, and there is no particular limitation. Examples of the step of devolatilizing and drying include heating and vacuum devolatilization.
[0156] [4. Molded body] The molded article according to one embodiment of the present invention (hereinafter, sometimes referred to as "the molded article") is obtained by molding the resin composition described in the above section [3. Resin composition]. The molded article has the advantage of being excellent in impact resistance.
[0157] (Impact resistance of molded body) The IZOD test result for the molded product at 23°C is 60 kJ / m 2 It is preferable that the concentration is 70 kJ / m or more. 2 More preferably, it is 75 kJ / m or more. 2 More preferably, it is 80 kJ / m or more. 2 It is particularly preferable that the impact resistance is 17 kJ / m or more. According to this configuration, the molded article has excellent impact resistance. In addition, the result of the IZOD test of the molded article at 0° C. is, but is not particularly limited to, 17 kJ / m 2 It is preferable that the concentration is 18 kJ / m or more. 2 More preferably, it is 19 kJ / m or more. 2More preferably, it is 20 kJ / m or more. 2 The measurement method of the IZOD test of the molded product at 23° C. or 0° C. will be described in detail in the Examples below.
[0158] (Method of Manufacturing Molded Product) In the method for producing a molded article according to one embodiment of the present invention, the molded article can be obtained by molding the resin composition described in the section [2. Resin composition].
[0159] The method for producing the present molded article is not particularly limited, but examples thereof include a rolling or pressing method, an extrusion molding method, and an injection molding method. EXAMPLES
[0160] Hereinafter, one embodiment of the present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited thereto. One embodiment of the present invention can be practiced with appropriate modifications within the scope of the above or below-mentioned purpose, and all of these modifications are included in the technical scope of the present invention. In the following, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".
[0161] First, various measurement and evaluation methods will be described.
[0162] [Measurement and evaluation methods] (Measurement of increase in polymerization conversion rate of monomer A per hour in elastomer polymerization process) In the elastomer polymerization process, the time from the start of elastomer polymerization (for example, the time when a polymerization initiator was added to monomer A) to the time when it was observed that the polymerization conversion rate of monomer A reached 80% or more was measured. Next, the value calculated by dividing the polymerization conversion rate (unit: %) at that time by the time (unit: hour) was defined as the increase per hour (% / hour) of the polymerization conversion rate of monomer A in the elastomer polymerization process. In the elastomer polymerization process, the increase in the polymerization conversion rate of monomer A per hour is 20.0 (% / hour) or less, so that the internal temperature and internal pressure can be controlled in the elastomer polymerization process, and the elastomer can be safely produced.
[0163] (Measurement of the converted polymerization time of elastomer) The value calculated by dividing 100% polymerization conversion by (the increase per hour in the polymerization conversion of monomer A in the elastomer polymerization step) was taken as the converted polymerization time of the elastomer.
[0164] (Evaluation of productivity of elastic bodies) In cases where the results of (Evaluation of controllability of internal temperature in elastomer polymerization process) and (Evaluation of internal pressure and its controllability in elastomer polymerization process) shown below are both 1 (passable), the productivity of the elastomer was evaluated based on the following evaluation method: 2 (Good): The conversion polymerization time of the elastic body is within 10 hours 1 (OK): The conversion polymerization time of the elastic body is more than 10 hours and less than 20 hours. 0 (Not acceptable): The conversion polymerization time of the elastomer exceeds 20 hours.
[0165] (Evaluation of internal temperature controllability in elastomer polymerization process) The controllability of the internal temperature in the elastomer polymerization process was evaluated based on the following evaluation method: 1 (OK): The internal temperature of the reaction vessel during the elastomer polymerization process can be controlled within ±5°C of the set value of the internal temperature of the reaction vessel. 0 (Not acceptable): The internal temperature of the reaction vessel during the elastomer polymerization process exceeds ±5°C of the set internal temperature of the reaction vessel. The internal temperature of the reaction vessel was measured by a temperature measuring device provided in the reaction vessel.
[0166] (Evaluation of internal pressure and its controllability in elastomer polymerization process) The controllability of the internal pressure in the elastomer polymerization process was evaluated based on the following evaluation method: 1 (OK): In the elastomer polymerization process, the internal pressure (gauge pressure) of the reaction vessel is 0 MPa to 0.8 MPa. 0 (Not possible): During the elastomer polymerization process, the internal pressure (gauge pressure) of the reaction vessel exceeds 0.8 MPa (the internal pressure of the reaction vessel cannot be controlled). The internal pressure of the reaction vessel was measured by a pressure detector provided in the reaction vessel.
[0167] (Measurement of volume average particle size) The volume average particle size was measured on a volume basis using a particle size distribution measuring device using dynamic light scattering ("Nanotrac Wave-EX150" manufactured by Nikkiso Co., Ltd.).
[0168] (Powder properties of polymer fine particles) About 20 g of the fine polymer particle powder obtained in each Example and Comparative Example was spread on a piece of paper, and the particle size range of the powder was measured using a scaled ruler. The powder properties of the granular material were evaluated according to the following criteria. Note that the larger the number, the more excellent the powder properties. 3: The particle size range of the powder is about 0.1 mm to about 0.5 mm. 2: The particle size range of the powder is about 0.1 mm to about 2.0 mm. 1: The particle size range of the powder is about 0.1 mm to about 5.0 mm.
[0169] (Creating test pieces for measuring impact resistance) 100 parts of polyvinyl chloride (Kaneka Corporation, "Kanevinyl S-1007") as a matrix resin, 1.0 part of a tin-based stabilizer (Nitto Kasei Corporation, "TVS#8831"), 0.8 parts of a lubricant (Emery Oleochemicals Japan, Inc., "Loxiol GH-4"), and 0.2 parts of a lubricant (Clariant Japan, Inc., "Wax-E") were heated to 110°C with stirring and cooled to room temperature (23°C) to obtain a mixture (total amount 102.0 parts).
[0170] To the resulting mixture, 10 parts of polymer fine particles (impact modifier) obtained in each of the following Examples or Comparative Examples were added per 100 parts of polyvinyl chloride to obtain a resin composition. The resulting resin composition was kneaded for 5 minutes at 155°C using a kneader equipped with two rolls ("8-inch mixing roll" manufactured by Nippon Roll Mfg. Co., Ltd.) to produce a sheet (molded product). Thereafter, using a heat press machine (37-ton press manufactured by Shinto Metal Works, Ltd.), the mixture was kneaded at 180°C and 70 kgf / cm. 2 The sheet was cut into test pieces (thickness 5 mm) for measuring impact resistance. The test pieces for measuring impact resistance conform to the JIS K 7110 standard.
[0171] (Measurement of impact resistance) An IZOD test was performed on an impact resistance test piece (thickness 5 mm) with a V notch at 23°C or 0°C to measure the impact resistance in accordance with JIS K 7110.
[0172] (Measurement of B method flow) The resin composition was filled into a cylinder at room temperature and 190°C, and a load of 300 kgf / cm was applied from a die (1 mmφ×10 mm). 2 The specimen was extruded by applying a pressure of 1000 V and the extrusion strength was measured.
[0173] Example 1 <Elastomeric Polymerization Process> 200 parts of water, 0.2 parts of tripotassium phosphate, and 5 parts of sodium lauryl sulfate were charged into a polymerization vessel equipped with a stirrer, and after nitrogen replacement, the temperature was raised to 60°C. 0.0094 parts of ferrous sulfate (FeSO4·7H2O), 0.0156 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.5 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel. Then, a mixed component consisting of 100 parts of β-farnesene (FA) and 1 part of 1,3-butylene glycol dimethacrylate as monomer A was added to the polymerization vessel in one go. As a polymerization initiator, 0.06 parts of paramenthane hydroperoxide was added immediately after the addition of the mixed component in one go (0 hours after the addition in one go, at the start of polymerization) and 9 times at 1-hour intervals immediately after the addition in one go. That is, a total of 0.6 parts by weight of paramenthane hydroperoxide was added. Ten hours after the addition (10 hours from the start of polymerization), the polymerization conversion rate reached 97%, and a latex containing an elastomer (PFR-1) with a volume average particle size of 30 nm was obtained. The solid content of the latex containing the elastomer (PFR-1) was 32%.
[0174] Seven hours after the start of polymerization, the polymerization conversion rate of monomer A reached 85%. The increase in the polymerization conversion rate of monomer A per hour was 12.2 (% / hour), and the equivalent polymerization time of the elastomer was 8.2 hours. There was no problem with the controllability of the internal temperature, and the elastomer could be polymerized at normal internal pressure.
[0175] <Graft polymerization step> 219 parts of latex containing elastomer (70 parts of elastomer) and water were charged into a polymerization vessel equipped with a stirrer. The amount of water charged here was such that the total amount of water contained in 219 parts of latex containing elastomer (PFR-1) was 300 parts. Next, the gas in the polymerization vessel was replaced with nitrogen, and the temperature in the polymerization vessel was raised to 60°C. Next, 0.0056 parts of ferrous sulfate (FeSO4·7H2O), 0.0094 parts of EDTA·2Na, and 0.2 parts of sodium formaldehyde sulfoxylate were added into the polymerization vessel. Next, a mixture of 20 parts of methyl methacrylate (MMA), 5 parts of butyl acrylate (BA), and 5 parts of styrene (St) as a monomer mixture for forming a graft portion, and 0.1 parts of tertiary butyl hydroperoxide as a polymerization initiator was continuously added into the polymerization vessel over 150 minutes.
[0176] After 10 minutes from the end of the addition of the mixture of the graft-forming monomer mixture and the polymerization initiator, 0.075 parts of sodium formaldehyde sulfoxylate and 10 minutes after that, 0.06 parts of t-butyl hydroperoxide were added to the polymerization vessel, and polymerization was continued for another 80 minutes. This operation produced a latex containing polymer fine particles (PFG-1) with a volume average particle size of 31 nm. The polymerization conversion was 96%, and the solid content of the latex was 24.8%.
[0177] <Production of powder and granular materials> 2.0 parts of an emulsified antioxidant was added to the latex containing the obtained polymer microparticles (PFG-1), and 2.0 parts of calcium chloride was further added at room temperature or below to coagulate the polymer microparticles. The amount of water in the obtained slurry was adjusted so that the slurry concentration was 10%, and then heat treatment was performed at 80°C to 90°C. Subsequently, the slurry was cooled to room temperature, and then dehydration treatment was performed to recover the coagulated material. The obtained coagulated material was subjected to drying treatment at 50°C to obtain powdered polymer microparticles, that is, powdered granules. Using the obtained powdered granules, a resin composition was produced according to the method described above (preparation of test pieces for impact resistance measurement), and further a test piece for impact resistance measurement was produced. The obtained test piece was measured for impact resistance by the above-mentioned method, and the B method flow was also measured. The results are shown in Tables 1 and 2 together with the composition of the polymer microparticles.
[0178] Example 2 <Elastomeric Polymerization Process> The elastomer was polymerized in the same manner as in Example 1, except that the initial amount of sodium lauryl sulfate was changed from 5 parts to 1 part, and the addition of 0.06 parts of paramenthane hydroperoxide every hour was changed to 13 times (total 14 times). At the 14th hour from the start of polymerization, the polymerization conversion rate reached 99%, and a latex containing an elastomer (PFR-2) with a volume average particle size of 48 nm was obtained. The solid content concentration of the latex containing the elastomer (PFR-2) was 32%.
[0179] Eight hours after the start of polymerization, the polymerization conversion rate reached 81%, the increase in the polymerization conversion rate of monomer A per hour was 10.1 (% / hour), and the conversion time for the elastomer was 9.9 hours. There was no problem with the controllability of the internal temperature, and the elastomer could be polymerized at normal internal pressure.
[0180] <Graft polymerization process, powder and granular production> The graft portion was polymerized by the same method as in Example 1, except that the latex containing the elastomer (PFR-2) was used so that the amount of the elastomer (PFR-2) was 70 parts. By this operation, a latex containing polymer fine particles (PFG-2) with a volume average particle diameter of 49 nm was obtained. The polymerization conversion rate was 99%, and the solid content concentration of the latex containing polymer fine particles (PFG-2) was 24.9%. By the same method as in Example 1, powdered polymer fine particles, i.e., powder particles, were obtained, and further a resin composition and a test piece for measuring impact resistance were obtained, and various physical properties were evaluated. The results are shown in Tables 1 and 2.
[0181] Example 3 <Elastomeric Polymerization Process> The elastomer was polymerized in the same manner as in Example 1, except that the vessel was changed to a pressure vessel with stirring, the amount of sodium lauryl sulfate was changed to 1 part, the mixed components added in one lump as monomer A were changed to 60 parts of β-farnesene and 40 parts of 1,3-butadiene, and the addition of 0.06 parts of paramenthane hydroperoxide every hour was changed to 8 times (total 9 times). At 9 hours from the start of polymerization, the polymerization conversion rate was 99%, and a latex containing an elastomer (PFR-3) with a volume average particle size of 48 nm was obtained. The solid content concentration of the latex containing the elastomer (PFR-3) was 32%. The polymerization conversion rate reached 80% 5.3 hours after the start of polymerization, the increase in the polymerization conversion rate of monomer A per hour was 15.2 (% / hour), and the conversion time of the elastomer was 6.6 hours. There was no problem with the controllability of the internal temperature, and the internal pressure reached a maximum 3 hours after the start of polymerization, at which time the internal pressure was 0.2 MPa (gauge pressure).
[0182] <Graft polymerization process, powder and granular production> The graft portion was polymerized by the same method as in Example 1, except that the latex containing the elastomer (PFR-3) was used so that the amount of the elastomer (PFR-3) was 70 parts. By this operation, a latex containing polymer fine particles (PFG-3) with a volume average particle diameter of 49 nm was obtained. The polymerization conversion rate was 99%, and the solid content concentration of the latex containing polymer fine particles (PFG-3) was 24.9%. By the same method as in Example 1, powdered polymer fine particles, i.e., powder particles, were obtained, and further a resin composition and a test piece for measuring impact resistance were obtained, and various physical properties were evaluated. The results are shown in Tables 1 and 2.
[0183] Example 4 <Elastomeric Polymerization Process> Except for using cumene hydroperoxide as a polymerization initiator, the elastomer was polymerized in the same manner as in Example 1. At 14 hours after the start of polymerization, the polymerization conversion rate reached 98%, and a latex containing an elastomer (PFR-4) with a volume average particle diameter of 44 nm was obtained. The solid content of the latex containing the elastomer (PFR-4) was 32%. The polymerization conversion rate reached 84% 12 hours after the start of polymerization, the increase in the polymerization conversion rate of monomer A per hour was 7.0 (% / hour), and the conversion time of the elastomer was 14.3 hours. There was no problem with the controllability of the internal temperature, and the elastomer could be polymerized at normal internal pressure.
[0184] <Graft polymerization process, powder and granular production> The graft portion was polymerized by the same method as in Example 1, except that a latex containing an elastomer (PFR-4) was used. By this operation, a latex containing polymer fine particles (PFG-4) with a volume average particle diameter of 45 nm was obtained. The polymerization conversion rate was 97%, and the solid content concentration of the latex containing polymer fine particles (PFG-4) was 25%. By the same method as in Example 1, powdered polymer fine particles, i.e., powder particles, were obtained, and further a resin composition and a test piece for measuring impact resistance were obtained, and various physical properties were evaluated. The results are shown in Tables 1 and 2.
[0185] Comparative Example 1 <Elastomeric Polymerization Process> 160 parts of water and 0.4 parts of tripotassium phosphate were charged into a pressure-resistant polymerization vessel equipped with a stirrer. After the temperature in the pressure-resistant polymerization vessel was raised to 40°C, 0.0048 parts of ferrous sulfate (FeSO4·7H2O), 0.0079 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.02 parts of sodium formaldehyde sulfoxylate were added into the pressure-resistant polymerization vessel. Next, after degassing the pressure-resistant polymerization vessel, 3.6 parts of sodium oleate were added into the pressure-resistant polymerization vessel, and further, a monomer mixture for forming an elastomer consisting of 90 parts of 1,3-butadiene and 10 parts of β-farnesene was added all at once into the pressure-resistant polymerization vessel. Then, 0.06 parts of paramenthane hydroperoxide was added into the pressure-resistant polymerization vessel to start the polymerization of the elastomer.
[0186] Two hours after the initiation of polymerization, 0.02 part of sodium formaldehyde sulfoxylate was added, and 3 hours later, 0.02 part of paramenthane hydroperoxide was added.
[0187] At 2.5 hours after the start of polymerization, the polymerization conversion rate reached 85%, the increase per hour in the polymerization conversion rate of the monomer mixture for forming the elastomer was 34.0 (% / hour), and the conversion time for the elastomer was 2.9 hours. The increase per hour in the polymerization conversion rate of the monomer mixture for forming the elastomer exceeded 20.0 (% / hour), and it was not possible to control the internal temperature and internal pressure. Therefore, it was not possible to carry out the graft polymerization process and the production of powder and granular materials.
[0188] Comparative Example 2 <Elastomeric Polymerization Process> 160 parts of water and 0.4 parts of tripotassium phosphate were charged into a pressure-resistant polymerization vessel equipped with a stirrer. After the temperature in the pressure-resistant polymerization vessel was raised to 40°C, 0.0048 parts of ferrous sulfate (FeSO4·7H2O), 0.0079 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.02 parts of sodium formaldehyde sulfoxylate were added into the pressure-resistant polymerization vessel. Next, after degassing the pressure-resistant polymerization vessel, 1.8 parts of sodium oleate were added into the pressure-resistant polymerization vessel, and further, a monomer mixture for forming an elastomer consisting of 90 parts of 1,3-butadiene and 10 parts of β-farnesene was added all at once into the pressure-resistant polymerization vessel. Then, 0.06 parts of paramenthane hydroperoxide was added into the pressure-resistant polymerization vessel to start the polymerization of the elastomer.
[0189] Two hours after the start of polymerization, 0.02 part of sodium formaldehyde sulfoxylate was added, 3 hours later, 0.02 part of paramenthan hydroperoxide was added, and 10 hours later, 0.2 part of sodium oleate was added, and the temperature was raised to 50°C. 0.02 part of paramenthan hydroperoxide was added at 12 hours, 0.03 part of paramenthan hydroperoxide at 13 hours, and 0.03 part of paramenthan hydroperoxide at 15 hours, and polymerization was continued.
[0190] At 16 hours after the start of polymerization, the polymerization conversion rate reached 99%, and a latex containing an elastomer (PBR-2) with a volume average particle size of 67 nm was obtained. The solid content of the latex containing the elastomer (PBR-2) was 39%.
[0191] The conversion rate reached 80% 12.8 hours after the start of polymerization, and the increase per hour in the polymerization conversion rate of the monomer mixture for forming the elastomer was 6.3 (% / hour). The conversion time for the elastomer was 16 hours, which was more than 10 hours, resulting in low productivity. There were no problems with the controllability of the internal temperature and pressure, and the internal pressure reached a steady state 3 hours after the start of polymerization, at which point the internal pressure was 0.3 MPa (gauge pressure).
[0192] <Graft polymerization process, powder and granular production> The graft portion was polymerized by the same method as in Example 1, except that the latex containing the elastomer (PBR-2) was used so that the amount of the elastomer (PBR-2) was 70 parts. By this operation, a latex containing polymer fine particles (PBG-2) with a volume average particle diameter of 77 nm was obtained. The polymerization conversion rate was 99%, and the solid content concentration of the latex containing polymer fine particles (PBG-2) was 24.9%. By the same method as in Example 1, powdered polymer fine particles, i.e., powder particles, were obtained, and further a resin composition and a test piece for measuring impact resistance were obtained, and various physical properties were evaluated. The results are shown in Tables 1 and 2.
[0193] Comparative Example 3 <Elastomeric Polymerization Process> 160 parts of water and 0.4 parts of tripotassium phosphate were charged into a pressure-resistant polymerization vessel equipped with a stirrer. After the temperature in the pressure-resistant polymerization vessel was raised to 40°C, 0.0048 parts of ferrous sulfate (FeSO4·7H2O), 0.0079 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.02 parts of sodium formaldehyde sulfoxylate were added into the pressure-resistant polymerization vessel. Next, after degassing the pressure-resistant polymerization vessel, 3.6 parts of sodium oleate were added into the pressure-resistant polymerization vessel, and further, a monomer mixture for forming an elastomer consisting of 100 parts of 1,3-butadiene was added all at once into the pressure-resistant polymerization vessel. Then, 0.06 parts of paramenthane hydroperoxide was added into the pressure-resistant polymerization vessel to start polymerization.
[0194] Two hours after the initiation of polymerization, 0.02 part of sodium formaldehyde sulfoxylate was added, and 3 hours later, 0.02 part of paramenthane hydroperoxide was added.
[0195] The polymerization conversion rate reached 80% two hours after the start of polymerization, the increase per hour in the polymerization conversion rate of the monomer mixture for forming the elastomer was 40.0 (% / hour), and the conversion time for the elastomer was 2.5 hours. The increase per hour in the polymerization conversion rate of the monomer mixture for forming the elastomer exceeded 20.0 (% / hour), and the internal temperature and internal pressure could not be controlled. As a result, the graft polymerization step and the production of powder and granular materials could not be carried out.
[0196] Comparative Example 4 <Elastomeric Polymerization Process> 160 parts of water and 0.4 parts of tripotassium phosphate were charged into a pressure-resistant polymerization vessel equipped with a stirrer. After the temperature in the pressure-resistant polymerization vessel was raised to 40°C, 0.0048 parts of ferrous sulfate (FeSO4·7H2O), 0.0079 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.02 parts of sodium formaldehyde sulfoxylate were added into the pressure-resistant polymerization vessel. Next, after degassing the pressure-resistant polymerization vessel, 1.8 parts of sodium oleate were added into the pressure-resistant polymerization vessel, and further, a monomer mixture for forming an elastomer consisting of 100 parts of 1,3-butadiene was added all at once into the pressure-resistant polymerization vessel. Then, 0.06 parts of paramenthane hydroperoxide was added into the pressure-resistant polymerization vessel to start polymerization of the elastomer.
[0197] Two hours after the start of polymerization, 0.02 part of sodium formaldehyde sulfoxylate was added, 3 hours later, 0.02 part of paramenthan hydroperoxide was added, and 10 hours later, 0.2 part of sodium oleate was added, and the temperature was raised to 50°C. 12 hours later, 0.02 part of paramenthan hydroperoxide was added, and 13 hours later, 0.03 part of paramenthan hydroperoxide was added, and polymerization was continued.
[0198] At 15 hours after the start of polymerization, the polymerization conversion rate reached 93%, and a latex containing an elastomer (PBR-4) with a volume average particle size of 83 nm was obtained. The solid content of the latex containing the elastomer (PBR-4) was 37%.
[0199] The polymerization conversion rate reached 80% 11 hours after the start of polymerization, the increase per hour in the polymerization conversion rate of the monomer mixture for forming the elastomer was 7.3 (% / hour), and the equivalent polymerization time for the elastomer was 13.6 hours. This exceeded 10 hours, resulting in low productivity. There were no problems with the controllability of the internal temperature and internal pressure, and the internal pressure reached a steady state 3 hours after the start of polymerization, at which point the internal pressure was 0.4 MPa (gauge pressure).
[0200] <Graft polymerization process, powder and granular production> The graft portion was polymerized in the same manner as in Example 1, except that the latex containing the elastomer (PBR-4) was used so that the amount of the elastomer (PBR-4) was 70 parts. By this operation, a latex of polymer fine particles (PBG-4) having a volume average particle diameter of 85 nm was obtained. The polymerization conversion rate was 99%, and the solid content concentration of the latex of the polymer fine particles (PBG-4) was 24.9%. By the same method as in Example 1, powdered polymer fine particles, i.e., powder particles, were obtained, and further a resin composition and a test piece for measuring impact resistance were obtained, and various physical properties were evaluated. The results are shown in Tables 1 and 2.
[0201] Comparative Example 5 <Elastomeric Polymerization Process> An elastomer was produced in the same manner as in Comparative Example 4, except that 100 parts of 1,3-butadiene was replaced with 29 parts of 1,3-butadiene, 42 parts of β-farnesene (FA), and 29 parts of styrene (St). This resulted in the production of a latex of elastomer (PFR-5) with a polymerization conversion rate of 95% of the components constituting the elastomer. The volume average particle size of the elastomer (PFR-5) was 50 nm, and the solid content of the latex of the elastomer (PFR-5) was 36%.
[0202] <Production of graft parts, production of powder and granules> 194 parts of latex containing elastomer (70 parts of elastomer) and water were charged into a pressure-resistant polymerization vessel equipped with a stirrer. Here, the amount of water charged was such that the total amount of water contained in 194 parts of latex containing elastomer (PFR-5) was 250 parts. Next, the gas in the pressure-resistant polymerization vessel was replaced with nitrogen, and the temperature in the pressure-resistant polymerization vessel was raised to 60°C. Next, 0.0056 parts of ferrous sulfate (FeSO4·7H2O), 0.0094 parts of EDTA·2Na, and 0.06 parts of sodium formaldehyde sulfoxylate were added to the pressure-resistant polymerization vessel, and the pressure-resistant polymerization vessel was degassed. Next, 15 parts of β-farnesene and 15 parts of 1,3-butadiene were charged in one go into the pressure-resistant polymerization vessel as a monomer mixture for forming the graft portion. Subsequently, 0.06 parts of paramenthane hydroperoxide was added as a polymerization initiator to initiate polymerization, and then paramenthane hydroperoxide was appropriately added to complete the polymerization. This operation resulted in a latex containing polymer fine particles (PFG-5) with a volume average particle diameter of 57 nm. The polymerization conversion rate was 100%, and the solid content concentration of the latex was 28%. Powdered polymer fine particles, i.e., powdered granules, were obtained by the same method as in Example 1, and further a resin composition and a test piece for measuring impact resistance were obtained, and various physical properties were evaluated. The results are shown in Tables 1 and 2.
[0203] [Table 1]
[0204] [Table 2]
[0205] <Consideration> The method for producing polymer microparticles according to one embodiment of the present invention includes an elastomer polymerization step of polymerizing a farnesene-containing monomer A to obtain an elastomer containing farnesene units and having a volume average particle size of less than 50 nm, and a graft polymerization step of polymerizing a graft portion to the elastomer, in which the increase in polymerization conversion rate of the monomer A per hour in the elastomer polymerization step is 20.0 (% / hour) or less. Therefore, the method for producing polymer microparticles according to one embodiment of the present invention can provide a method for producing polymer microparticles having excellent controllability of internal temperature and internal pressure in the elastomer polymerization step, as shown in Table 1. Furthermore, the method for producing polymer microparticles according to one embodiment of the present invention can also provide a method for producing polymer microparticles having excellent productivity, as shown in Table 1. Furthermore, the method for producing polymer microparticles according to one embodiment of the present invention can also provide polymer microparticles that can provide a resin composition having excellent flowability and a molded product having excellent impact resistance, as shown in Table 2. The polymer microparticles obtained by the method for producing polymer microparticles according to one embodiment of the present invention can also provide a powdered granule having excellent powder properties, as shown in Table 2. [Industrial Applicability]
[0206] The polymer microparticles obtained by the method for producing polymer microparticles according to one embodiment of the present invention can be preferably used in various applications such as adhesives, coating materials, molded articles, films, etc., by being blended with a matrix resin. Specifically, the polymer microparticles can be preferably used for stationery applications, food packaging applications, electrical and electronic applications, building materials applications, vehicle applications, etc.
Claims
1. an elastomer polymerization step of polymerizing a farnesene-containing monomer A to obtain an elastomer containing farnesene units and having a volume average particle size of less than 50 nm; A graft portion polymerization step of polymerizing a graft portion onto the elastomer, In the elastomer polymerization step, The method for producing polymer microparticles, wherein an increase in the polymerization conversion rate of the monomer A per hour is 20.0 (% / hour) or less.
2. the polymer microparticles have the elastomer and the graft portion, 2. The method for producing polymer microparticles according to claim 1, wherein the graft portion contains more than 80% by weight of vinyl units in 100% by weight of constituent units.
3. 2. The method for producing polymer microparticles according to claim 1, wherein in the elastomer polymerization step, the polymerization initiator comprises paramenthane hydroperoxide.
4. 2. The method for producing polymer microparticles according to claim 1, wherein an increase in the polymerization conversion rate of the monomer A per hour is 5.0 (% / hour) or more.
5. 2. The method for producing polymer microparticles according to claim 1, wherein the elastomer comprises one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units and polyfunctional units.
6. The elastic body contains, based on 100% by weight of the constituent units, Contains 5.0% to 99.9% by weight of farnesene units; and The method for producing polymer microparticles according to claim 1, wherein the polymer microparticles contain, in total, 0.1% by weight to 95.0% by weight of one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units and polyfunctional units.
7. The elastic body contains, based on 100% by weight of the constituent units, The composition contains 0% by weight to 95.0% by weight of diene units other than the farnesene units, The vinyl unit is contained in an amount of 0% by weight to 50.0% by weight, and The method for producing polymer microparticles according to claim 6, wherein the polyfunctional unit is contained in an amount of 0 to 20.0% by weight.
8. The elastomer does not contain a styrene unit, and The method for producing polymer microparticles according to claim 1 , wherein the graft portion contains a styrene unit.
9. 9. The method for producing polymer microparticles according to claim 1, wherein the graft portion contains a styrene unit and / or an alkyl (meth)acrylate unit.
Citation Information
Patent Citations
Coated polymer particles, resin modifier, rubber composition, and tire
WO2017038724A1